Investigating the potential mechanism of microneedling in alopecia areata mice based on 16S rRNA sequencing and metabolomics - Zhang, Yue; Li, Lu; Cao, Lei; Xia, Rushan (Frontiers in Microbiology, 2025)
BackgroundThe present study investigates the relationship between alopecia areata (AA) and intestinal microecology, examining the effect of microneedling on the microecology of alopecia areata.MethodsAn animal model of AA was established using imiquimod-induced C3H/HeJ mice. Halometasone was applied topically every 2 days for 2 weeks after a hand-held dermal microneedling treatment. Fecal samples were collected before and after the interventions and underwent 16S rRNA high-throughput sequencing to assess intestinal microecological alterations. Furthermore, changes in short-chain fatty acids (SCFA) associated with AA and microneedling treatment were analyzed.ResultsMicroneedling therapy enhanced hair growth in the model group. The model group exhibited a substantial decline in diversity and abundance of gut microbes compared to the control group. After microneedling treatment, the diversity of intestinal microbes was restored, along with a concurrent remodeling of both pathogenic and beneficial bacterial compositions in the model group. In addition, the levels of acetic acid and propanoic acid were elevated in the model group compared to the control group. Following microneedling treatment, a reduction in these levels was observed. In contrast, the model group showed an increase in butanoic acid levels after microneedling treatment; however, this increase did not reach statistical significance.ConclusionMicroneedling treatment has been shown to improve hair regeneration in AA. Additionally, it positively affects the intestinal microecology related to AA, leading to changes in gut microbes and the production of SCFAs. This provides a foundation for the clinical application of microneedling treatment in AA.